Antioxidant activity and mechanism of action of sesamol in triacylglycerols and fatty acid methyl esters of sesame, olive, and canola oils. (April 2019) - Toorani, Mohamad Reza; Farhoosh, Reza; Golmakani, Mohamadtaghi; Sharif, Ali
Abstract: The kinetics of the oxidation of triacylglycerols and fatty acid methyl esters of sesame, olive, and canola oils were concomitantly investigated in presence of different concentrations of sesamol at 60 °C. In addition to the inhibition of peroxyl radicals, sesamol and its radical were likely to pro-oxidatively attack lipid hydroperoxides and substrates, respectively. The highest antioxidant activity of sesamol in triacylglycerols was found in the sesame oil from which sesamol naturally originates, followed by in the triacylglycerols of olive and canola oils. Sesamol was of higher antioxidant activity in the fatty acid methyl esters than in their triacylglycerols. Due to the destructured triacylglycerol backbones, sesamol exerted a lower antioxidant activity in fatty acid methyl esters of sesame oil than in those of canola and olive oils, respectively. Highlights: Analysis of sesamol activity with concomitant respect to the free radical and interfacial phenomena. Clarification of the mechanism of antioxidant action of sesamol in lipid systems of different unsaturation degree. Elucidation of the effect of triacylglycerol structure on the antioxidant activity of sesamol.